A natureza das práticas de governança corporativa no Brasil - Andrade, Filipe José Dal'Bó de (2016)
This study describes the evolution of corporate governance practices in brazilian firms between 2010 and 2014 and investigates market and operational elements that predicts firms decisions in adopting best or worst practices. Thereunto, data were collected from primary sources and then were used to generate the Corporate Governance Quality Index (CGQI), composed by four elements: Board Structure; Board Procedure; Minority Shareholder Rights and; Disclosure. Results show a constant evolution in the corporate governance practices over time. There is evidence that the firms recognize the benefits of adopting good practices, as one observes greater evolution amplitude between firms of Novo Mercado, Level 1 and Bovespa Mais segments. The greater evolution occurs in the practices related to the Board Structure and Procedure. Between the market and operational elements, highlights that the most profitable firms looks to adopting better practices of corporate governance and better practices of Disclosure in their informations. Firms listed in the Level 1 and Traditionalsegments, where there is greater tangibility in its operations, shows better practices related to the Board Structure and Procedure. Riskier firms adopt better practices related to the Minority Shareholder Rights